Distributed Learning Ecosystems: Concepts, Resources, and Repositories - Daniel Otto, Gianna Scharnberg, Michael Kerres, Olaf Zawacki-Richter (Springer Nature, 2023)
This open-access book is based on the observation that learning ecosystems are increasingly established in higher education institutions. However, an important aspect that is still missing is their interconnectedness. Consequently, the book intends to close this gap by introducing the concept of a distributed learning ecosystem (DLE). A DLE follows the idea of establishing an interlinkage between decentralised learning ecosystems (consisting of content repositories and educational resources) and thus serves as an integrated approach that enables learners to access and use learning content and share resources.